Predictive Role of Body Image in Bulimic Behaviors Among Obese Patients Qualified for Bariatric Surgery - Bȩtkowska-Korpała, Barbara; Ćwiȩk, Aleksandra; Izydorczyk, Bernadetta; Starowicz-Filip, Anna; Major, Piotr (Frontiers in Psychiatry, 2021)
Abstract Background In the course of surgical treatment of obesity, bulimic behaviour and the associated experience of one's own body are of great importance. Objective This study aimed to determine the predictive role of multidimensional body image on bulimic-type eating behaviours in individuals scheduled for surgical treatment of obesity. Method The study was conducted in a clinical setting on a group of 100 obese patients treated at the Centre for the Surgical Treatment of Obesity at the University Hospital in Krakow (Poland), qualified for bariatric surgery. Body image was examined with Cash's Multidimensional Body-Self Relations Questionnaire (MBSRQ) and bulimic behaviour with David M. Garner's Eating Attitudes Test (EAT- 26), but in part A only with the Bulimia and food preoccupation scale and part B. Gender, age and BMI were included in the predictive models. A stepwise multiple regression analysis was used to assess psychological predictors of eating behaviours, and for binary variables - a logistic regression analysis was used for the whole group and for the women's group only. Due to the small number of men in this subgroup, regression analyses were not performed. Results In the analyses, higher values were observed in the dimension of AO-Appearance Orientation in women compared to men. AE - Appearance Evaluation and age were found to be significant predictors for bulimic behaviours in the whole group. In regression models for behaviour in the last six months, the predictors were found to be HE - Health Evaluation and AO - Appearance Orientation for laxative use and OWP - Overweight Preoccupation for vomiting for weight control. In contrast, behaviours treated as health-promoting in obesity treatment were conditioned as follows: for exercise, the predictors were gender and FO - Fitness orientation, for weight loss - OWP - Overweight preoccupation and BAS - Body areas satisfaction. Conclusion Our research indicates that different bulimic behaviours are variously conditioned by body image dimensions. Some body image dimensions are predictors of behaviours that are risk factors for obesity and poor outcomes of bariatric treatment, while other dimensions increase the chance of pro-health behaviours for obese individuals.